Identification of transfer function to model brush temperature of a small DC machine at no-load - Muhammad Syawal, Mat Jahak; Ismayuzri, Ishak; Suhaimi, Puteh; Sutiman, .; I. Wayan, Adiyasa (Penerbit UMP, 2023)
Using temperature measurement to provide insight into the health condition of an electrical machine at any operating point could be possible if a baseline temperature of the machine could be modelled in real-time and compared to the actual current temperature. In this study, transfer functions are being identified to be used as a baseline temperature response model for a small DC machine. As a preliminary study, the transfer functions are identified using experimental data of temperature responses at several no-load speed step inputs. The order of transfer function tested was between a range from 0 to 4. The third order transfer function was found to be the best followed by the first order transfer function with a model MSE error of less than 0.41 and 0.65 respectively. The slight variation on the poles of the system indicates that the thermal system of the electrical machine does not obey exactly the LTI hypothesis.